Interwoven Sound Spaces - Full Concert - 21 December 2022 - Live Streaming Camera at Konzertsaal der UdK Berlin ... - Visi, Federico; Greinke, Berit; Scarlat, Chris; Leisen, Moritz (Zenodo, 2023)
Recording of the live streaming of the Interwoven Sound Spaces telematic music performance concert. This is the footage captured by the videocamera placed at Konzertsaal der UdK Berlin, Berlin, Germany. Interwoven Sound Spaces is an interdisciplinary project which brought bringing together telematic music performance, interactive textiles, interaction design, and artistic research. A team of researchers collaborated with two professional contemporary music ensembles based in Berlin, Germany, and Piteå, Sweden, and four composers, with the aim of creating a telematic distributed concert taking place simultaneously in two concert halls and online. Central to the project was the development of interactive textiles capable of sensing the musicians’ movements while playing acoustic instruments, and generating data the composers used in their works. Musicians, instruments, textiles, sounds, halls, and data formed a network of entities and agencies that was is reconfigured for each piece, showing how networked ...